2015
DOI: 10.1039/c5ra13104a
|View full text |Cite
|
Sign up to set email alerts
|

Indium oxide nanocluster doped TiO2 catalyst for activation of molecular O2

Abstract: The In2O3 nanocluster doped faceted nanosize anatase TiO2 can activate molecular O2 for styrene epoxidation reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
1
3
0
4
Order By: Relevance
“…It may be due to the coordination of indium metal with DMF and the coordination may activate molecular oxygen . From the experiment, it came to an end that a suitable reaction condition is required for the optimum performance of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be due to the coordination of indium metal with DMF and the coordination may activate molecular oxygen . From the experiment, it came to an end that a suitable reaction condition is required for the optimum performance of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was found that indium doped mesoporous silica and mesoporous oxides can activate molecular oxygen to form the epoxides. Indium metal dispersed over silica matrix was found to be the activator of molecular oxygen, however, the role of support has not studied thoroughly.…”
Section: Introductionmentioning
confidence: 99%
“…Metal oxide nanocluster finds its promising applications in optical and sensors [1], optoelectronics [2], photocatalysts [3] and biomedical applications [4]. Till now, there have been a considerable number of reports for the fabrication of various metal oxide nanocluster, such as ZnO [5][6][7][8], TiO 2 [1,3,9], SnO 2 [10][11][12][13], In 2 O 3 [14][15][16], CuO 2 [17][18][19], WO 3 [20,21]. The reported technique for the synthesis includes (a) physical synthesis such as pulsed laser deposition [5], glancing angle deposition [2], cluster beam deposition [22], and others; (b) chemical synthesis such as sol-gel [9], hydrothermal decomposition [18], and others; (c) biological synthesis using agro wastes, algal media, plant extract, fungi, yeast, and others.…”
Section: Introductionmentioning
confidence: 99%
“…De acordo com esses autores, a diminuição da área específica de superfície em materiais contendo índio ocorreu, principalmente, em virtude das variações na porosidade dos catalisadores de forma que maiores valores de volume de poros levam a maiores áreas específicas de superfície nos catalisadores não modificados (AMOLI et al, 2015;LOU et al, 2014).…”
Section: Resultsunclassified
“…Além disso, no caso específico dos materiais contendo céria, é possível perceber que apesar dos catalisadores Cu/CeO2-5%In e Cu/CeO2-10%In apresentarem volume de poros muito próximos, há uma diferença entre suas áreas específicas de superfície que pode ser explicada pelas diferenças no tamanho de partícula (AMOLI et al, 2015;LOU et al, 2014).…”
Section: Resultsunclassified